Analisis Pengaruh Brand Image Terhadap Keputusan Pembelian Konsumen pada Momoyo di Kota Padangsidimpuan - Masnia Silitonga; Maeka Rosianna Tarihoran (Trending: Jurnal Manajemen dan Ekonomi, 2024)
This study aims to analyze the influence of brand image on consumer purchasing decisions on the Momoyo brand in Padangsidimpuan City. The research method used is descriptive qualitative with in-depth interview techniques with consumers and direct observation. Data were analyzed using data reduction, data presentation, and conclusion drawing methods. The results of the study indicate that brand image has a significant role in influencing consumer decisions to purchase Momoyo products. Factors such as product quality, brand reputation, and marketing communications contribute to the positive image of the Momoyo brand. Consumers tend to choose Momoyo over other products because of their positive perceptions of the brand.